Comparison of Serum Vitamin D Level between Outdoor and Indoor Working Professionals and Its Correlation with Serum Parathyroid Hormone Level - Tasrin, Tarana; Siddiquea, Arbin; Hossain, Nafisa; Mozaffor, Miliva (Journal of Bangladesh Society of Physiologist, 2024)
Background: Parathyroid hormone (PTH) is functionally linked to vitamin D for calcium homeostasis in our body. Objective: To compare serum vitamin D level between outdoor and indoor working professionals of Dhaka city, Bangladesh, and observe its correlation with serum PTH level. Methods: This cross-sectional, analytical study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka, Bangladesh, from July 2018 to June 2019. A total of 101 indoor and outdoor professional workers of both sexes working in different sectors living in Dhaka city participated in this study. They were divided into two groups –outdoor workers (n=35) and indoor workers (n=66) Estimations of both serum vitamin D3 and PTH were done using chemiluminescence microparticle immunoassay method. Statistical analysis was done by students unpaired t tests and Pearson correlation coefficient test. Results: Among outdoor workers, mostly hailed from Traffic Police Services (83%) and the rest (17%). were street hawkers. Indoor workers were recruited from the hospital – nurses (32%), doctors (27%), administrative employees (21%), hospital ward assistants (12%) and medical technicians (8%). Sufficient and insufficient levels of serum D3 were observed more in outdoor professional workers than indoor (P<0.05) whereas deficient levels of serum D3 was found more in indoor workers than outdoor workers (P<0.001). Mean serum vitamin D3 level was found significantly (P<0.001).higher in outdoor workers than that of indoor workers (19.35±5.67ng/ml vs. 14.17±4.18ng/ml) but mean serum PTH level was not significantly different (P>0.05)r in outdoor workers than that of indoor workers (42.35±18.27 vs. 37.78±17.54); Moreover, there was no significant correlation between serum vitamin D and parathyroid hormone levels in both outdoor (r= +0.290; p >0.05) and indoor (r= –0.206; p>0.05) groups .Conclusion: Our data concluded that indoor working professionals were more prone to develop vitamin D deficiency although outdoor working professionals may be affected with vitamin D insufficiency. In addition, there may be no relationship between serum vitamin D and parathyroid hormone levels even in D deficient indoor workers. J Bangladesh Soc Physiol 2022;17(2): 78-84